Teaching English in multicultural classrooms - Muhamad, Ainon Jariah (2009)
The English language classroom provides an obvious multicultural context for learning, and teachers need to help students understand and appreciate the differences and similarities among the various ethnic, religious and cultural groups. This study aims to examine teachers’ understanding of and attitudes towards multiculturalism, and in so doing, find out what are the language teaching strategies used in promoting and enhancing successful multicultural interactions. Teachers should be able to seize this opportunity to foster tolerance and understanding in classrooms of diverse cultural backgrounds.